A Liquid Membrane as a Barrier Membrane for Guided Bone Regeneration. (12th June 2011) - Kim, Daesung; Kang, Taeheon; Gober, Daniel; Orlich, Chad
Abstract : Membranes made of several different materials are available in the market, nonresorbable (e.g. ePTFE), resorbable (e.g. synthetic or collagen) and liguid applicable (e.g. Polyethylene glycol or Atrisorb). The purpose of the present study was to evaluate whether or not in situ application of Atrisorb could be used as a barrier membrane for guided bone regeneration. Ten patients with insufficient alveolar ridge width for implant placement participated in the study. Atrisorb in conjunction with various bone grafts was used to treat 10 different sites, 3 sites treated prior to implant placement and 7 sites in conjunction with implant placement. Augmented sites were allowed to heal for 3 to 7 months, with mean healing time of 4.7 months. Healing was uneventful with no major complications. Two sites experienced a flap dehiscence accompanied by barrier exposure during the initial healing period. Secondary healing was achieved soon after with no signs of infection, giving Atrisorb a barrier exposure rate of 20% for the present study, which corresponds to favorably to that of resorbable membranes. The liquid membrane has the potential of being a viable alternative to traditional resorbable membranes for use in GBR procedures.